2020
DOI: 10.5293/ijfms.2020.13.1.012
|View full text |Cite
|
Sign up to set email alerts
|

RANS and LES Simulations at Partial Load in Francis Turbines : Three-Dimensional Topology and Dynamic Behaviour of Inter-Blade Vortices

Abstract: Hydraulic machines are designed to operate in flow conditions close to the best efficiency point. However, to respond to the increasing demand for flexibility mainly due to the integration of renewable energy in the electric grid, the operating range of Francis turbines has to be extended towards smaller discharge levels without restriction. When Francis turbines are operated typically between 30% and 60% of the rated output power, the flow field is characterized by the appearance of inter-blade vortices in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The closer it is to the upper crown position, the closer the vortex structure is to the runner inlet. The same phenomenon was found in related experiments [20] and CFD simulations [21][22][23].…”
Section: Test Results Of Different Sectionssupporting
confidence: 86%
“…The closer it is to the upper crown position, the closer the vortex structure is to the runner inlet. The same phenomenon was found in related experiments [20] and CFD simulations [21][22][23].…”
Section: Test Results Of Different Sectionssupporting
confidence: 86%
“…Cheng [40][41][42] demonstrated that applying large eddy simulation to the Francis turbine has notable advantages over other methods.…”
Section: Les Numerical Modelmentioning
confidence: 99%
“…To maintain grid stability and perform both primary and secondary load balancing functions, hydraulic turbines are an essential part of energy conversion technologies [3]. Hydraulic turbines can be modified to match the total energy output to the energy demand at any given moment [4]. Hydraulic turbines must operate in a very wide operating range with a decent level of safety and without experiencing excessive vibrations to achieve this goal [1].…”
Section: Introduction 11 Hydro Turbine and Off-design Conditionsmentioning
confidence: 99%